Differences in the reduction of coliform bacteria and escherichia coli with the chlorine diffuser method combined with silica sand in clean water - Rizal, Afrian Muhammad; Asyfiradayati, Rezania (Science Midwifery, 2024)
For all living things, including humans, water is a very important need. Problems that are often found include groundwater or rivers owned by the community that do not meet the criteria to provide clean and safe drinking water. The objective was to determine the difference in the decrease of Coliform and Escherichia coli bacteria by the Chlorine Diffuser method combined with silica sand in clean water for 30, 45, 60 minutes. The method used was a quasi-experiment with a pretest-postest with control design. Samples were taken in one of the wells in the Golilan area. The analysis uses One Way Annova with a sig of 95%. The results showed that there was a difference in the number of Coliform bacteria with a treatment time with a sig value of 0.000, but there was no difference in the number of Escherichia coli bacteria with a treatment time with a sig value of 0.659